2011
DOI: 10.5402/2011/314209
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phenazine 5,10-Dioxides Release OH in Simulated Hypoxia and Induce Reduction of Tumour Volume In Vivo

Abstract: Phenazine 5,10-dioxides (PDOs) are a new class of bioreductive cytotoxins, which could act towards tumours containing hypoxic regions. The PDOs selective-hypoxic bioreduction was probed in vitro; however, the mechanism of action has not been completely explained. Besides, PDOs in vivo antitumour activities have not been demonstrated hitherto. We study the mechanism of hypoxic/normoxic cytotoxicity of PDO representative members. Electron spin resonance is used to confirm •OH production, alkaline comet assay to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…In reference to the predicted ADMET properties we analyzed human intestinal absorption (HIA), Caco‐2 permeability, ability to be substrate or inhibit P‐glycoprotein, renal organic cation transporter (OCT2) inhibition, ability to be substrate or inhibit CYP450s, human ether‐a‐go‐go‐related gene (hERG) inhibition, in vitro mutagenicity, and in vivo clastogenicity and effects as carcinogen. On the other hand, we predicted the aqueous solubility (LogS) due to the solubility problems observed previously with this kind of compounds (Table ) . Concerning to the absorption and distribution aspects, the predicted parameters, i. e. HIA and Caco‐2 permeability, indicated that 1 could be orally administered (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In reference to the predicted ADMET properties we analyzed human intestinal absorption (HIA), Caco‐2 permeability, ability to be substrate or inhibit P‐glycoprotein, renal organic cation transporter (OCT2) inhibition, ability to be substrate or inhibit CYP450s, human ether‐a‐go‐go‐related gene (hERG) inhibition, in vitro mutagenicity, and in vivo clastogenicity and effects as carcinogen. On the other hand, we predicted the aqueous solubility (LogS) due to the solubility problems observed previously with this kind of compounds (Table ) . Concerning to the absorption and distribution aspects, the predicted parameters, i. e. HIA and Caco‐2 permeability, indicated that 1 could be orally administered (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the aqueous solubility limitations observed previously with some phenazine dioxides and the predicted medium LogS for 1 (Table ), we studied the solubilization of 1 using a mixture of sterile physiological saline:polysorbate 80 (Tween TM 80) (4:1, v/v) as an alternative formulation to improve the bioavailability and adequate tumor‐biodistribution. Tween 80 has been widely used in biochemical applications including solubilizing proteins and emulsifying and dispersing substances and drugs in medicinal and food products .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 However, it does not show any obvious hypoxia-selective effects as the free radicals generated by phenazine 5,10-dioxides could not induce apoptosis in Caco-2 cells. 62 Moreover, several novel derivatives of phenazine 5,10dioxides have been synthesized to investigate the inhibition rate between DNA and topoisomerase II, showing cytotoxicity in V79 cells in both hypoxic and normoxic environments. 63 Some of these derivatives illustrated cytotoxicity but did not exhibit hypoxia specificity.…”
Section: N-oxidesmentioning
confidence: 99%
“…1-4 in Figure 1a). [4][5][6][7][8][9][10][11] Furthermore, recently phenazine dioxides with improve DNA interaction capacity features an increased planar -conjugation or flexible moieties that add to DNAstacking. 12,13 12 used conventional conditions by heating the phenol or amine intermediate in acetonitrile in presence of potassium carbonate as base.…”
Section: Introductionmentioning
confidence: 99%